Morphology of the pupae of Physonota humilis Boheman and Physonota stigmatilis Boheman (Coleoptera: Chrysomelidae: Cassidinae: Ischyrosonychini) - López-Pérez, Sara; Rodríguez-Mirón, Geovanni M.; Chaboo, Caroline S. (Zootaxa, 2021)
Pupal morphology has been described for 11 species in six genera of the Neotropical tortoise beetle tribe, Ischyrosonychini Chapuis, 1875. This life stage may offer valuable phylogenetic information but more pupae need to be documented. The pupae of Physonota humilis Boheman, 1856 and P. stigmatilis Boheman, 1854 are described and illustrated for the first time. The pupa of P. humilis does not exhibit lateral scoli on the abdominal segments. Additionally, the body surfaces of P. humilis and P. stigmatilis are somewhat tuberculate, different from other described Physonota Boheman, 1854 pupae. A key to the described pupae of Physonota is provided and 10 phylogenetic character hypotheses are proposed.